Sociodemographic and occupational influences on health professionals' quality of life - Alberto de Oliveira Redü; Daiani Modernel Xavier; Marcela Amaral Daoud; Pâmela Kath de Oliveira Nörnberg; Natália Sperli Geraldes Marin dos Santos Sasaki; Geovane Mendes Farias; Luciano Garcia Lourenção (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To analyze the sociodemographic and occupational influences on health professionals' quality of life. Method: This descriptive-exploratory, cross-sectional, analytical, and quantitative study addressed 94 health workers, including nursing technicians, nurses, and physical therapists working in Intensive Care Units in a town in the extreme south of Brazil in 2023. The student's t-test and Spearman correlation were used. Results: A significant positive correlation was found between being a woman and the psychological domain and between income and the social and environmental domain while working hours were inversely related to general QoL. Additionally, workload negatively impacted the physical, psychological, and general QOL, furniture negatively influenced the psychological domain, and equipment was negatively associated with the physical and psychological domain. Conclusion: The characteristics of the work environment interfere with several areas of quality of life.